ADVISABILITY AND POSSIBILITY OF USING ICT DURING PREPARATION FOR THE EIA IN MATHEMATICS - Shkolnyi, O.; Tykhonenko, Yu (Fizyko-matematychna osvita, 2021)
Formulation of the problem. At present, any researches on the methodology of organizing and conducting external independent assessment of academic achievements in mathematics of Ukrainian graduates has become extremely relevant. In particular, this is due to the fact that from 2021 the EIA in mathematics is mandatory in the system of state final attestation. The aim of this work is to determine the advisability and possibility of using information and communication technologies in preparation for the EIA in mathematics. To achieve this goal, we organized a statistical survey of students, the results of which can then be used to create guidelines for professionals in preparation for independent assessment. Materials and methods. To achieve the goals of the article, we use empirical methods: our own survey using an electronic tool (Google form), monitoring the learning process of students, as well as analysis of their achievements results. In the paper we use the set of scientific cognition methods: comparative analysis to clarify different views on the problem; systematization and generalization to formulate conclusions and methodological advices; generalization of the author's pedagogical experience and observations. Results. According to the survey of Ukrainian graduates, most of them choose a combined approach in preparation for the EIA in mathematics, i.e. use both electronic learning tools and printed textbooks. Most students prefer to prepare for testing with a tutor or on the special offline courses. Independent preparation is mostly inherent for students of classes and schools of physical and mathematical profile. More than 80% of respondents have a positive attitude for using of e-learning tools in preparation for the EIA, and the most popular of them are online test platforms and video tutorials on YouTube. 64% of surveyed students are satisfied with their own level of preparation for the EIA in mathematics, and among the reasons for dissatisfaction are the lack of knowledge and skills acquired at school. However, most respondents believe that preparation for the EIA should be completely provided by the state on a free basis. At the same time, the main way to improve the system of preparation for external examination students consider the need for funding of teachers and test participants. Conclusions. Electronic aids in preparation for the external examination in mathematics are still unpopular. The reason for this may be the low level of technology dissemination in our country. That is why offline courses and tutors are the most typical choice of entrants in preparation for the EIA. The willingness of students to pay tutors shows the current inability of the state to provide students with the necessary level of knowledge in general and for the EIA in particular within the school curriculum. Thus, in Ukraine there is a situation when the "shadow" education system dominates in quality and popularity over the official one. The problem facing the state is how to regulate the shadow sector of educational services in such way that it does not hinders, but helps and contributes to ensuring the proper quality of education.